Comparative Evaluation of Dimensional Accuracy Between Digital And Conventional Impression Techniques For Parallel Endosseous Dental Implants - Amer Oussama Kanj; Abd El Hadi Usama Kanj (International Journal of Computational and Experimental Science and Engineering, 2025)
The precision of dental impressions is of utmost importance for the successful construction of implant-supported prostheses. This research compares parallel endosseous dental implant digital and conventional impression techniques in terms of dimensional accuracy.60 impressions (30 digital and 30 conventional) were taken on a master model with parallel implants. Digital impressions were taken with an intraoral scanner, and conventional impressions were taken with polyvinyl siloxane (PVS) material. The accuracy of both methods was assessed by comparing deviations in implant position and angulation with a coordinate measuring machine (CMM).Digital impressions had far lower mean deviations in implant position (25 ± 5 µm) than conventional impressions (45 ± 10 µm). The angular deviations were lower for digital impressions (0.2° ± 0.05°) than for conventional impressions (0.5° ± 0.1°). Detailed comparisons of linear and angular deviations were presented on six tables.Digital impression techniques demonstrated superior dimensional accuracy for parallel endosseous dental implants compared to conventional techniques.